Downregulation of Clusterin Expression in Human Testicular Seminoma - Bianjiang Liu; Min Tang; Zhijian Han; Jiexiu Zhang; Pei Lu; Jie Li; Ninghong Song; Zengjun Wang; Changjun Yin; Wei Zhang (Cellular Physiology and Biochemistry, 2013)
Background: Clusterin, a heterodimeric glycoprotein of approximately 80 kDa, exists extensively in human body fluids. The abnormal expression of clusterin is closely related to the occurrence, progression, and prognosis of tumors. Up to now, few studies have focused on clusterin in human testicular cancer. This study describes an extensive exploration of the presence and expression of clusterin in testicular seminoma. Methods: Tumor tissues and normal testis tissues were collected from 13 patients with testicular seminoma and 16 patients undergoing surgical castration for prostate cancer. Real-time polymerase chain reaction (PCR) was performed to detect the expression difference of clusterin mRNA between testicular seminoma and normal testis. Western blot and immunohistochemical analysis were performed to detect the presence and expression difference of clusterin protein between two groups. Results: Real-time PCR showed the expression of clusterin mRNA in testicular seminoma to be significantly lower than in normal testis (only 13% relative quantification). Western blot analysis indicated marked reductions in the expression of clusterin protein in testicular seminoma. Similar results were observed upon immunohistochemical analysis. Conclusion: In testicular seminoma and normal testis, clusterin exists in its heterodimeric secretory isoform. Clusterin expression is significantly lower in testicular seminoma than in normal testis. This is the first comprehensive study of the presence and expression of clusterin in human testicular cancer.